On Improvement of the Weather Information Management in Uganda - Sansa Otim, Julianne; Waisswa, Milton (UbuntuNet-Connect, 2012)
Weather forecasts are used to make important decisions (e.g. reduce crop damage, reduce property damage, save lives, safety in the aviation industry) that can enhance a country's economy. This paper presents the challenges faced in managing Uganda's weather information which are: a sparse meteorology network, manual data processing and lack of access to the weather information by most stakeholders. This paper then goes ahead to propose an integrated approach that combines off-theshelf (cheap) wireless sensor technology, free satellite data, earth science grid infrastructure and mobile computing to address the identified challenges. It is anticipated that these efforts will improve accessibility and accuracy of weather information to all that need it and hence have a positive impact on the economy.
Keywords: Weather forecasts; Earth science grids; Weather information dissemination; Uganda